Double perovskite Ca2GdNbO6:Mn4+ deep red phosphor: Potential application for warm W-LEDs - Lu, Zuizhi; Huang, Tianjiao; Deng, Ruopeng; Wang, Huan; Wen, Lingling; Huang, Meixin; Zhou, Liya; Yao, Chunying (Superlattices and microstructures, 2018)
A novel Mn4+-doped Ca2GdNbO6 (CGN) phosphor was prepared by high-temperature solid-state reaction. The crystal structure was investigated by X-ray diffraction patterns and unit cell structure. Mn4+ replaced the location of Nb5+ in the CGN lattice, and the value of energy gap (Egap) decreased from 2.16 eV to 1.13 eV, indicating that Mn4+ ions play a great influence on the absorption of CGN hosts. The broad excitation band from 250 nm to 550 nm matches well with commercial near-UV light emitting diodes, and the emission peak centered at 680 nm is due to 2E→4A2g transition in Mn4+ ions. The CIE chromaticity coordinates (0.698, 0.303) of CGN:Mn4+ phosphor was close to standard red color coordinates (0.666, 0.333). These investigations demonstrate CGN:Mn4+ phosphor as an efficient red phosphor for potential applications. [Display omitted] •Red phosphors Ca2GdNbO6:Mn4+ phosphors were synthesized for the first time.•Board excitation bands can be efficiently excited by near-UV light to emit deep red emission.•Tanabe−Sugano energy level diagram is used to analysis the luminescence mechanism.•Temperature dependence spectra is investigated to demonstrate its good thermal stability.